First characterization of gastrointestinal culturable bacteria of Patagonian toothfish Dissostichus eleginoides (Nototheniidae) - Urtubia, Rocio; Gallardo, Pablo; Cárdenas, César A.; Lavin, Paris; González Aravena, Marcelo (Revista de Biología Marina y Oceanografía, 2019)
The Patagonian toothfish Dissostichus eleginoides is one of the most important fisheries from the Southern Ocean. The biology of this species is relatively well studied and some nutritionals issues have also been reported; however there is no information about the composition of the bacterial community of the gastrointestinal tract, which is essential to characterize the microbiota of this fish. The bacterial flora of D. eleginoides is here described for the first time using culturable methods. By applying traditional culture-based techniques and 16S rDNA sequencing methods it was possible to characterize the families Vibronaceae and Moraxellaceae, which were mainly represented by Vibrio and Psychrobacter, respectively. This Patagonian fish shows a microbiota very similar to other cold waters fishes.